THE AI PARADOX IN CENTRAL BANKING: NEW POWERS, NEW VULNERABILITIES - Koroye, Tamarakemiebi; Alaekwe, Sydney (Bank Indonesia, 2025)
The integration of artificial intelligence into central banking disrupts the traditional bank regulator relationship, creating asymmetries that private institutions exploit. This paper examines how AI-driven market surveillance and predictive risk modelling erode private banks’ informational advantages, compelling them into a Schumpeterian race for survival in which innovation becomes imperative. Using a qualitative analysis of regulatory developments and financial market adaptations, this study argues that enhanced central bank AI capabilities paradoxically accelerate the emergence of opaque financial segments designed to evade oversight. The findings indicate that this shift transforms regulatory dynamics, positioning central banks as real-time market participants while private institutions develop increasingly sophisticated methods of regulatory evasion. This evolution generates systemic risks that existing regulatory frameworks struggle to address, necessitating adaptive oversight mechanisms. The study concludes that the imperative progressively drives financial innovation to maintain opacity in response to algorithmic supervision, underscoring the need for regulatory models that balance AI’s benefits with emerging vulnerabilities.